Influence of Antioxidant Sericin in Tris Extender on Oxidative Markers during Cryopreservation (–196ºC) of Bovine Semen - Patel, Tapasvi M; Dhami, AJ; Chaudhari, DV; Pathan, MM (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
This investigation was carried out during winter season on the semen of three mature, healthy breeding bulls each of Gir cattle and  Murrah buffalo breeds. The aim was to assess the effect of different concentration of antioxidant Sericin (0.0, 0.1, 0.25, 0.50 and 1.0%,  w/v) in standard tris fructose egg yolk glycerol (TFYG) extender on cryopreservability of bovine semen based on sperm motility and  oxidative markers in seminal plasma of freshly diluted and cryopreserved semen. The mean sperm motility observed in freshly diluted  and frozen-thawed Gir bull semen, irrespective of Sericin levels, were 76.93 ± 0.39 and 43.47 ± 0.58% and in Murrah bulls 78.20 ± 0.38 and 44.10 ± 0.48%, respectively. The values of malondialdehyde (MDA, µmol/ml) in seminal plasma of freshly diluted and frozen-thawed  semen of Gir bulls, irrespective of Sericin levels, were 21.68 ± 0.38 and 24.99 ± 0.56, and in Murrah bulls 21.49 ± 0.57 and 25.60 ± 0.94,  respectively. The corresponding values of superoxide dismutase (SOD, U/ml) were 1.77 ± 0.06 and 1.37 ± 0.05 in Gir and 1.18 ± 0.06  and 0.85 ± 0.04 in Murrah bulls, and those of glutathione peroxidase (GPx, nmol/min/ml) 417.10 ± 12.00 and 349.76 ± 11.92 in Gir and  385.71 ± 9.21 and 320.02 ± 9.49 in Murrah bull semen. Sperm motility and activities of all three enzymes differed highly significantly  (p
Keywords: Antioxidant; Bovine semen; Cryopreservation; Oxidative markers; Sericin; Sperm motility